Evaluation of differences at high intensity threshold and its performance value during the most valuable soccer championships in Europe - Izzo, R.; Hosseini Varde, S.; Sopranzetti, S.; Cejudo, A.; Cruciani, A.; Giovanelli, M. (Journal of Physical Education and Sport, 2021)
The sports performance of footballers during games and training has been the subject of research for years.Nowadays thanks to the new technologies applied to the match analysis, is possible to highlightperformance using statistical-mathematical criteria. Recent studies support that not only the phase of the match spent at high speeds are determinants, but even each instant in which the acceleration and deceleration values cross above the high intensity thresholds.Our research seeks essentially to add, in the literature, a specific study, concerning quantity and quality of work expressed on these parameters, above the high intensity thresholds, in the various European elite championships.The search raises 26 players for each match (including substitutes), 260 athletes per championship, for a total of 1300 players (average age 28.4 years, height 1.79 meters, weight kg 78) and 9100 parameters data.The high intensity parameters evaluated are:Distance covered at high intensity (> 16 Km/h); Distance covered in Acceleration (> 2m/s²); Distance covered in Deceleration (< -2m/s²); Distance covered a MP> 20 Watt / Kg; Average AMP; D = Total Distance; Drel = distance/minute. Data shows that the comparison in French league is balanced, that is high intensity activity is equal for winning and losing teams, in German and Italian championship, winning teams work below the high intensity threshold compared with losers, in the English and Spanish league winning teams work upper the high intensity threshold respect to losers. This confirms that the efficiency of sport performance, in case of football the victory of competition or matches, is not directly dependent only on the ability to carry out high-intensity activities and also supports the lack of specific training aimed at promoting the development of such skills. A more specific investigation directed at the analysis of only winning teams and losing teams in all championships showed a no decisive difference in high intensity parameters. In the chart below, it is highlighted that the high intensity activity is greater in the parameters of D_AccHI and D_DecHI in the winning teams than the losers (5-6%).